The Aesthetics of the Posthuman Human: Reflections Following Nietzsche’s Thus Spoke Zarathustra - Steinmann, Michael (Journal of Posthumanism, 2022)
Posthuman aesthetics leads to a decentering of the human and shows aspects of existence that are no longer contained in the categories and dichotomies that define the essence of the human being. But because all aesthetic involves human experience, a posthuman conception also needs to develop its own idea of the human being. The essay shows that the posthuman human can emerge along the lines of three categorical distinctions to the traditional idea of the human. It can emerge in the animal, which is similar to, but also fundamentally different from the human being; in the angelic which transcends the ordinary human in a powerful and joyful way; and in the demonic which overcomes human experience in a transgressive and potentially terrifying way. The essay follows Nietzsche’s Thus Spoke Zarathustra in which these dimensions of existence are described as a new, alien and ecstatic way of being human.